INTERACTION EFFECTS OF NITROGEN, PHOSPHORUS, AND ZINC FERTILIZATION ON GROWTH, YIELD, AND NUTRIENT CONTENTS OF LOWLAND RICE VARIETIES - Olanrewaju Emmanuel Oni; Nurudeen Adeyemi; Samuel Osunleti; Olanrewaju Ologunde; Ayodamola Fagoroye (Agricultura)
This study explored the effects of nitrogen, phosphorus, and zinc fertilization on two lowland rice varieties, NERICA L-34 and ARICA-3, in a screenhouse experiment at the Federal University of Agriculture, Abeokuta, Nigeria. Two levels each of nitrogen (0 and 120 kg ha-1), phosphorus (0 and 60 kg ha-1), and zinc (0 and 10 kg ha-1) were applied. Results indicated that the (N120 P60 Zn10) treatment produced the highest panicle weight (28.3g), grains per panicle (202.2), and 1000 grain weight (27.1g), leading to superior grain yield, dry weight, and harvest index. ARICA-3 showed the best panicle weight under specific treatments, while NERICA L-34 achieved the highest grain yield with other nutrient combinations. The study highlights the need for tailored nutrient management based on varietal responses and genetic factors to enhance rice productivity and address nutrient deficiencies.